Managed care: concepts and strategies for quality assurance (2013)
To understand the significance of quality assurance in Managed Care, there is need to examine the various relationships, strategies and ethics that exist within its system. Several types of managed care systems have gained popularity in the American health care system. Managed care plans adopt a number of techniques; some are directed at the behavior of physicians while others are directed at subscribers to the plan. Knowledge of the impact of legislative reforms such as HIP PA Act, Medicare and Medicaid on managed care is essential to understand physician-patient relationships. This research is exploratory because it utilizes existing literature and body of knowledge in health care to conclude that it is important to start reducing the risks of inappropriate financial incentives that may threaten the delivery of quality health care, as patient advocates must preserve fundamental duty of physicians